Speech Acts of Requests: A Case of Indonesian EFL Learners - Arif Nugroho; Agnira Rekha (Journal of English Language Teaching and Linguistics, 2020)
This study sheds light on the delineation of the most frequently used request strategies as realized by Indonesian EFL learners and their reasons of utilizing such strategies. A descriptive qualitative study was employed by involving forty (40) English learners of a university at Surakarta as the participants. The data were gathered by means of DCT-questionnaire, Role-plays, and Focus Group Discussion (FGD). The obtained data were descriptively analyzed by referring to Blum-Kulka and Olshtain’s Cross-Cultural Study of Speech Act Realization Patterns (CCSARP) followed by transcribing the result of FGD. The findings illustrated that Indonesian EFL learners made use of conventionally indirect request more frequently than other strategies. Furthermore, the FGD revealed that their reasons of employing conventionally indirect strategy were because of the cultural factors and the social distance between the interlocutors. As an effort to equip EFL learners with adequate pragmatic competence, this study offers some input enhancement both in terms of process (teaching activities) and in terms of product (realizing speech act of requests) for ELT practices in Indonesian context.